2019
DOI: 10.1016/j.jfma.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of vertical root fracture through intentional replantation and root fragment bonding with 4-META/MMA-TBB resin

Abstract: For a VRF tooth, in addition to tooth extraction, intentional replantation combined with root fragment bonding with 4-META/MMA-TBB resin is a successful treatment modality that can be used to preserve a complete VRF tooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Extraction was previously considered the only feasible treatment option for vertically fractured teeth [ 24 ]. However, many successful reimplantation cases, with reattachment followed up for 1–4 years, have been reported recently [ 8 , 15 18 , 20 ]. Nizam et al [ 19 ] reported promising clinical findings for the reimplantation of 21 vertically fractured maxillary incisors reattached using 4-META/MMA-TBB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extraction was previously considered the only feasible treatment option for vertically fractured teeth [ 24 ]. However, many successful reimplantation cases, with reattachment followed up for 1–4 years, have been reported recently [ 8 , 15 18 , 20 ]. Nizam et al [ 19 ] reported promising clinical findings for the reimplantation of 21 vertically fractured maxillary incisors reattached using 4-META/MMA-TBB.…”
Section: Discussionmentioning
confidence: 99%
“…With the advantages of modern endodontics, it is possible to treat various VRF cases [ 15 20 ]. Cone beam computed tomography has proved more helpful than periapical radiographs in diagnosing and monitoring VRF [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent reports have used intentional replantation to enable extraoral bonding of teeth with vertical root fractures (Hayashi et al 2002, 2004, Nizam et al 2016, Sugaya et al 2016, Okaguchi et al 2018, Rosen et al 2018) or to treat teeth considered as having a periodontally hopeless prognosis (Hou et al 2016, Solakoglu & Filippi 2017, Saida et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when adhesion healthy dentin surfaces, it was thought that increasing the thickness of the adhesive material on the fracture surface can get increase the mechanical strength [13,14]. In this method, intentional replantation is used in combination, and adhesion surfaces are formed in a hand-held situation, and a core resin is fill to the completely dried root canal surface [15,16]. In this report, the procedures and prognosis of the new treatment for the vertical tooth root fracture tooth reconstructed by intracanal adhesion method by intentional replantation.…”
Section: Introductionmentioning
confidence: 99%